Caries prevalence in 12-year-old Cypriot children - Panagidis, Dimos; Schulte, Andreas G. (Community dental health, 2012)
To determine caries prevalence and caries experience in 12-year-old children living in the Republic of Cyprus and to evaluate whether different variables were associated with caries experience. According to the WHO recommendation, schools were randomly selected by taking into account the distribution between rural and urban regions, so that 10% of Cypriot children attending the sixth grade could be examined. In the school year 2003/2004 the children were examined in schools by one person with the aid of artificial light but without taking radiographs or fibre-optic transillumination. DMFT, presence of fissure sealants and black stain were recorded. In total 951 children were examined. Caries prevalence was 32.6% (95% CI 29.62-35.6). The mean DMFT was 0.65 (sd 1.17) and the SiC was 1.95. Fissure sealants were found in 14.3% of the children. No association between frequency of tooth brushing, presence of fissure sealants or presence of black stain and caries experience was observed. Children living in rural areas had significantly higher mean DMFT values than children living in urban areas. A further caries decline may be attained by promoting a more extensive use of preventive measures like application of fluoride varnish or fissure sealants.
Gesehen am 05.06.2018